A high performance martensitic stainless steel containing 1.5 wt% Si. (5th July 2017) - Jiang, Tao; Sun, Junjie; Liu, Hongji; Wang, Yingjun; Guo, Shengwu; Sun, Yu; Liu, Yongning
Abstract: Usually, martensitic precipitation hardening stainless steels (MPHSSs) contain ultralow carbon concentration to ensure its high performance in corrosion resistance, weldability and toughness. Meanwhile, high content of alloy elements (such as Mo, Ni, Ti and Cu) is inevitably added in order to obtain superb strength by precipitation hardening. In this work, a new idea of alloying design in stainless steels has been proposed, in which carbon serves as the main strengthening element and high silicon concentration (1.5 wt%) is used to suppress carbide precipitation and coarsening during tempering. A steel with composition of Fe-0.2C-15Cr-3Ni-1.5Si-1.0Mn has been designed and prepared, and its excellent mechanical performance (ultimate tensile strength of 1680 MPa, total elongation of 16%), pitting corrosion resistance and weldability have been displayed. Moreover only low-cost alloying components and ordinary treatments are needed to obtain those outstanding properties which are comparable to commercialized MPHSSs (such as 17–4 PH, PH 13–8 Mo). Highlights: A new idea of alloying design in martensitic stainless steels has been proposed. High silicon concentration is used to suppress carbide precipitation and coarsening. This martensitic stainless steel possesses excellent comprehensive performance and enjoys the advantage of a lower cost. The microstructure is typical lath martensite with some retained austenite and nanoscale carbides dispersing in matrix.